The kinematic similarity of the triple jump and associated training drills - Simpson, S.; Wilson, C.; Kerwin, D. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
The triple jump is a complex sporting movement consisting of three phases with the aim of maximising total jump distance. The ground contacts preceding the hop, step and jump phases largely determine the subsequent flight distances. The transition between the hop and step phases is said to be the most critical element in triple jumping performance (Jurgens, 1998) and the minimisation of horizontal momentum losses during ground contacts has been linked to successful performance (Hay, 1992). Triple jumpers employ a variety of drills to help facilitate the effective execution of the ground contacts between each of the phases. These drills attempt to expose the performer to the physical demands of the movement and to replicate the movement patterns that occur thereby serving the specificity training principle identified by Matveyev (1981). The first aim of this study was to quantify the losses in horizontal momentum during the hop-step transition and hence to assess the subsequent effect on performance. The second aim of the study was to identify which of the training drills used by triple jumpers most closely match the movement patterns utilised within a triple jump performance during this critical transition.